RESURSELE INVESTIŢIONALE ALE ASIGURĂTORULUI: ROL ŞI IMPORTANŢĂ - Ulian, Galina (CEP USM, 2007)
Factors that make possible the placing of insurance reserves of insurers are investigated in this research. Afterwards, in this work were examined the principles to promote their investment policies. Deep analysis of investment instruments of national insurers was made simultaneously. Also, a profound research of investment portfolios structures of occidental insurers was carried out. In this context there were established some priority directions of optimization of investment policies promoted by national insurers.
Keywords: societăți de asigurări; politica investiţională